2020
DOI: 10.1186/s13071-020-04366-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced biosurveillance of high-consequence invasive pests: southern cattle fever ticks, Rhipicephalus (Boophilus) microplus, on livestock and wildlife

Abstract: Background Some tick species are invasive and of high consequence to public and veterinary health. Socioeconomic development of rural parts of the USA was enabled partly through the eradication by 1943 of cattle fever ticks (CFT, Rhipicephalus (Boophilus) annulatus and R. (B.) microplus). The southern cattle fever ticks (SCFT, R. (B.) microplus) remain a real and present threat to the USA animal agriculture because they are established in Mexico. Livestock-wildlife interactions in the Permanent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…To investigate potential causal mechanisms responsible for wildlife-mediated impacts on SCFT eradication efforts, we used the model described by Wang et al [ 18 , 20 ]. The model is spatially explicit and individual-based [ 25 , 26 ], and is designed to simulate effects of shifts in the spatiotemporal patterns of host (cattle, white-tailed deer, and nilgai) habitat use on the dynamics of SCFT populations (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To investigate potential causal mechanisms responsible for wildlife-mediated impacts on SCFT eradication efforts, we used the model described by Wang et al [ 18 , 20 ]. The model is spatially explicit and individual-based [ 25 , 26 ], and is designed to simulate effects of shifts in the spatiotemporal patterns of host (cattle, white-tailed deer, and nilgai) habitat use on the dynamics of SCFT populations (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…There is a wide variety of CFT models focused on questions dealing with both basic biology and management on four continents [ 15 ]. However, relatively few models have included explicit representation of wildlife hosts [ 16 – 19 ], and only one has included nilgai [ 20 ]. Based on results of a simulation modeling study focused on CFT–livestock–wildlife interactions, it has been suggested that refugia for CFT could be created by white-tailed deer during acaricide treatments directed at cattle via deposition and subsequent collection of CFT in habitats favorable for survival of off-host life stages [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Serologic and molecular evidence suggests that WTD in northern Mexico and southern Texas carry bovine babesiosis [ 17 ], and genetic data suggest WTD likely serve as a source for tick populations that will eventually feed on cattle [ 18 ]. Both field and modeling studies have examined the potential role of ungulate hosts related to disease transmission [ 19 ], the effects of seasonal fluctuations in host communities on the dynamics of infectious disease [ 20 ], and the efficacy of targeting acaricides at specific types of hosts [ 21 ]. Wang et al [ 10 ] focused specifically on modeling the impact of interactions between cattle and WTD on SCFT-eradication methods.…”
Section: Introductionmentioning
confidence: 99%